Multifunctional multilayer graphene/elastomer nanocomposites. (October 2015) - Frasca, D.; Schulze, D.; Wachtendorf, V.; Huth, C.; Schartel, B.
Abstract : Graphical abstract: Highlights: Multilayer graphene is a good nanofiller for elastomers. Multilayer graphene improves the rheological, curing and mechanical properties and the weathering stability of elastomers. The effect of the nanofiller is evident already at low concentration. Abstract: Elastomers are usually reinforced and employed in different applications. Various different nanoparticles, including layered silicates, carbon nanotubes, and expanded graphite, are currently being used as nanofiller. Multilayer Graphene (MLG) is proposed as promising nanofiller to improve the functional properties of Chlorine-Isobutylene-Isoprene Rubber (CIIR), Nitrile-Butadiene Rubber (NBR), Natural Rubber (NR) and Styrene–Butadiene Rubber (SBR) at low concentrations. MLG is constituted by only approximately 10 graphene sheets. Nanocomposites with extremely low MLG content (3 phr) showed evident improvement in rheological, mechanical and curing properties. The Young's modulus of the nanocomposites increased more than twice in comparison with the unfilled rubbers. MLG also improved the weathering resistance of the different rubbers. The nanocomposites conserved their initial mechanical properties against weathering exposure.